How do privileged insiders become change agents? A study of institutional volition - Feront, Cecile (Graduate School of Business (GSB), 2021)
While we have a sense of why institutionally marginalized individuals or dominant actors become change agents, it is less clear what motivates privileged insiders - those who have reaped advantages from existing institutional arrangements because of their education, their socio-economic background, their citizenship, their gender, or their race. I combine a symbolic interactionist perspective on social conduct with a structural perspective on frames to explore the process of institutional volition and the conditions under which privileged insiders may become engaged in different types of institutional change work to address societal issues. Institutional volition is the reflective process leading people to engage in purposeful efforts to shape or transform dominant institutional arrangements. My study reveals variances in the institutional volition of privileged insiders that explains why some of these actors engage in work to repair institutions, while others engage in work to transform them, either disrupting or creating institutions. My study draws attention to the distinct role of feelings rather than emotions in determining whether and how privileged insiders engage in institutional change work. It also suggests that these actors commit to transformative change when they acknowledge their complicity in the perpetuation of institutional injustices. Finally, I show that privileged insiders need to reframe their role in order to use it as a resource to engage in institutional disruption or creation work.